Fines Migration During CO2 Injection: A Review of the Phenomenon and New Breakthrough - Yusof, M.A.M. (Society of Petroleum Engineers, 2022)
Large volume of CO2 injection into the saline aquifer is considered to be the high potential CO2 storage method. Until now, the field of CO2 injectivity has been completely dominated by salt precipitation â and by far the most studied mechanism for the loss of injectivity. In this paper, our aim is to focus on recent findings on CO2 injectivity impairment by fines migration that should not be overlooked. This paper summarizes the state-of-the-art knowledge obtained from theoretical, field studies, and experimental observations on CO2 injectivity impairment by fines migration in saline aquifers in the sense of CO2 storage. By gathering various data from books, DOE papers, field reports and SPE publications, a detailed and high quality data set for fines migration during CO2 injection into saline aquifer is created. Key reservoir/fluid/rock information, operational parameters and petrophysical evaluations are assessments are provided, providing the basis for comprehensive data analysis. The results are presented in terms of boxplot and histogram, where histogram displays the distribution of each parameter and identifies the best suitable ranges for best practices; boxplots are used to detect the special cases and summarize the ranges of each parameter. Previous coreflooding experiments concluded that salt precipitation, mineral precipitation, dissolution and mobilization are the main mechanisms that caused CO2 injectivity impairments. Dissolution of carbonate minerals is dominant and it increases the poro spaces and connectivity of sandstone core samples. Conversely, detachment, precipitation of salt and clay minerals and deposition of fines particles decreases the flow are and even clog the flow paths despite net dissolution. However, the results are case dependent and lack generality in terms of quantifying the petrophysical damage. It has been highlighted that injection scheme (flow rate, time frame), mineral composition (clay content, sensitive minerals), particulate process in porous media (pore geometry, particle and carrier fluid properties), and thermodynamic conditions (pressure, temperature, salinity, CO2 and brine composition) give substantial effect on the fines migration during CO2 injection. Additionally, the current experimental work is limited to rendering time and difficult to identify the dynamic process of fines migration during CO2 injection. A list of potential additional work has therefore been presented in this paper including the establishment of microscopic visualization of CO2-brine-rock interactions with representative pore-network under reservoir pressure and temperature. This is the first paper to summarize the contribution of fines migration on CO2 injectivity impairment in saline aquifer. Copyright 2022, Society of Petroleum Engineers.